An experimental study of circular sand–water wall jets. (September 2015) - Azimi, Amir H.; Qian, Yu; Zhu, David Z.; Rajaratnam, Nallamuthu
Highlights: Mean and turbulence characteristics of sand phase were measured for sand–water wall jets. Centerline sand velocities of large particles are 15% higher than the small particles. A modified Verhoff's formulation can model sand velocity in vertical direction. A peak sand concentration was detected at x / d  = 5 and it was 1 /6 d above the bed. Turbulence intensity of sand–water wall jets is 34% less than that of single-phase wall jets. Abstract: Laboratory experiments were carried out to study the effects of sand particles on circular sand–water wall jets. Mean and turbulence characteristics of sand particles in the sand–water wall jets were measured for different sand concentrations co ranging from 0.5% to 2.5%. Effects of sand particle size on the centerline sand velocity of the jets were evaluated for sand size ranging from 0.21 mm to 0.54 mm. Interesting results with the range of measurements are presented in this paper. It was found that the centerline sand velocity of the wall jets with larger particle size were 15% higher than the jets with smaller particle size. Concentration profiles in the vertical direction showed a peak value at x / d  = 5 (where x is the longitudinal distance from the nozzle and d is the nozzle diameter) and the sand concentration decreased linearly for x / d  > 5. Experimental results showed that the turbulence level enhanced from the nozzle to x / d  = 10. For sand–water wall jets with a higher concentration ( co   = 1.5–2.5%), the turbulence intensity became smaller than the corresponding single-phase wall jets by 34% due to turbulent modulation. A modified logarithmic formulation was introduced to model the longitudinal turbulent intensity at the centerline and along the axis of the jet.